Local chemical origin of ferroelectric behavior in wurtzite nitrides. Issue 46 (18th October 2022) - Yazawa, Keisuke; Mangum, John S.; Gorai, Prashun; Brennecka, Geoff L.; Zakutayev, Andriy
Abstract : Combinatorial Al1− x Sc x N library decouples composition, crystal structure, and ferroelectric properties. The local chemical bonding is the key factor to control ferroelectric properties rather than extended crystal structure. Abstract : Ferroelectricity enables key modern technologies from non-volatile memory to precision ultrasound. The first known wurtzite ferroelectric Al1− x Sc x N has recently attracted attention because of its robust ferroelectricity and Si process compatibility, but the chemical and structural origins of ferroelectricity in wurtzite materials are not yet fully understood. Here we show that ferroelectric behavior in wurtzite nitrides has local chemical rather than extended structural origin. According to our coupled experimental and computational results, the local bond ionicity and ionic displacement, rather than simply the change in the lattice parameter of the wurtzite structure, is key to controlling the macroscopic ferroelectric response in these materials. Across gradients in composition and thickness of 0 < x < 0.35 and 140–260 nm, respectively, in combinatorial thin films of Al1− x Sc x N, the pure wurtzite phase exhibits a similar c / a ratio regardless of the Sc content due to elastic interaction with neighboring crystals. The coercive field and spontaneous polarization significantly decrease with increasing Sc content despite this invariant c / a ratio. This property change is due to the more ionic bonding nature of Sc–N relative to the more covalent Al–N bonds, and the local displacement of the neighboring Al atoms caused by Sc substitution, according to DFT calculations. Based on these insights, ionicity engineering is introduced as an approach to reduce coercive field of Al1− x Sc x N for memory and other applications and to control ferroelectric properties in other wurtzites.